Economic growth in Latin America and the Caribbean : growth transitions rather than steady states - Gutiérrez, Mario (CEPAL SantiagoCL, 2007)
Provides a statistical framework to analyzing the growth story of Latin America. Focuses on growth transitions and on the role played by investment and by national and foreign saving during growth transitions. Identifies transitions affecting investment and national and foreign savings rates. Identifies also, common amd country-specific transitions, based on comparisions of a sample group of eight Latin American countries with the Latin American and Caribbean region as a whole for the period 1960-2005.